2011
DOI: 10.1093/hmg/ddr327
|View full text |Cite
|
Sign up to set email alerts
|

The accumulation of un-repairable DNA damage in laminopathy progeria fibroblasts is caused by ROS generation and is prevented by treatment with N-acetyl cysteine

Abstract: Fibroblasts from patients with the severe laminopathy diseases, restrictive dermopathy (RD) and Hutchinson Gilford progeria syndrome (HGPS), are characterized by poor growth in culture, the presence of abnormally shaped nuclei and the accumulation of DNA double-strand breaks (DSB). Here we show that the accumulation of DSB and poor growth of the fibroblasts but not the presence of abnormally shaped nuclei are caused by elevated levels of reactive oxygen species (ROS) and greater sensitivity to oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
127
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(142 citation statements)
references
References 37 publications
13
127
1
1
Order By: Relevance
“…These findings are consistent with recent observations showing that oxidant exposure to lamin A thiols, as occurs during exposure to ROS or during cell senescence, results in lamin oxidation at conserved cysteines (Pekovic et al, 2011). Conversely, patients with LMNA mutations exhibit increased sensitivity to oxidative stress and show elevated ROS levels (Malhas et al, 2009;Pekovic et al, 2011;Richards et al, 2011;Sieprath et al, 2012). Lamin B1 also plays a role in oxidative stress; for example, lamin B1 expression decreases under conditions of chronic oxidative stress and this decrease alters the anti-oxidant protein expression through regulation of p53 or Oct-1 (Malhas et al, 2009).…”
Section: Mechanisms Involved In Lamin Aggregate Formationsupporting
confidence: 92%
“…These findings are consistent with recent observations showing that oxidant exposure to lamin A thiols, as occurs during exposure to ROS or during cell senescence, results in lamin oxidation at conserved cysteines (Pekovic et al, 2011). Conversely, patients with LMNA mutations exhibit increased sensitivity to oxidative stress and show elevated ROS levels (Malhas et al, 2009;Pekovic et al, 2011;Richards et al, 2011;Sieprath et al, 2012). Lamin B1 also plays a role in oxidative stress; for example, lamin B1 expression decreases under conditions of chronic oxidative stress and this decrease alters the anti-oxidant protein expression through regulation of p53 or Oct-1 (Malhas et al, 2009).…”
Section: Mechanisms Involved In Lamin Aggregate Formationsupporting
confidence: 92%
“…However, an appropriate mechanism of response, involving accumulation of proper levels of prelamin A, might help CE cells to survive long-lasting stress stimuli through modulation of chromatin arrangement and availability of the DNA-repair machinery. Moreover, and in agreement with the proposed protective role of lamins, it has been recently demonstrated that oxidation of cysteine residues in the lamin A tail protects cells from oxidative-stress-induced damage, whereas knockdown of lamin A accelerates ROS accumulation and causes cellular senescence (Richards et al, 2011). In this context, accumulation of proper levels of prelamin A during healthy ageing might increase the availability of mature lamin A (which can be promptly processed, without the need for transcription and translation), which could act as a sink for ROS at the nuclear envelope.…”
Section: Discussionsupporting
confidence: 73%
“…The latter form is accumulated in laminopathies resulting in premature ageing . At the cellular level, accumulation of farnesylated prelamin A is associated with nuclear enlargement, heterochromatin loss and euchromatin dispersion, increase in reactive oxygen species (ROS) (Richards et al, 2011) and activation of the p53 pathway (Muteliefu et al, 2012). A physiological role of prelamin A in muscle and adipose tissue differentiation (Capanni et al, 2005;Mattioli et al, 2011) and smooth muscle cell ageing has been reported (Ragnauth et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the accumulation of DNA damage in laminopathy progeria seems to be due to ROS generation, as an antioxidant treatment reduced the basal level of double-stranded DNA breaks. 56 Consistently, other studies showed accumulation of prelamin A after oxidative stress and the accumulation of prelamin A disrupt mitosis and induce DNA damage. 57 Additionally, our data suggest that oxidative stress, regardless of the cause, increases the level of lamin B1 to protect against ROS.…”
Section: Acknowledgmentssupporting
confidence: 62%